Ecosystemic Advocacy for Elementary Mental Health. Issue 1 (4th March 2022) - Brown, Regina N.; Gruman, Diana H.; Purgason, Lucy L.
Systemic inequity in education compels school counselors to widen their scope of advocacy beyond their local school environment. Fortunately, the tools of evidence-based, data-driven school counseling can be scaled up to influence change in larger systems. We present an advocacy project undertaken by an elementary school counselor who was alarmed by a significant increase in children's mental health concerns. She initiated a state-wide survey of school counselors that revealed a dire need for mental health support at the elementary level. Using an ecological framework, we report on the data-driven advocacy actions she pursued to raise awareness of the serious concerns of young students across her state.